Intracranial Volume and Whole Brain Volume in Infants With Unicoronal Craniosynostosis - Hill, Cheryl A. (2010)
OBJECTIVE: Craniosynostosis has been hypothesized to result in alterations of the brain and cerebral blood flow due to reduced intracranial volume, potentially leading to cognitive deficits. In this study we test the hypothesis that intracranial volume and whole brain volume in infants with unilateral coronal synostosis differs from those in unaffected infants. DESIGN: Our study sample consists of magnetic resonance images acquired from 7- to 72-week-old infants with right unilateral coronal synostosis prior to surgery (n = 10) and age-matched unaffected infants (n = 10). We used Analyze 9.0 software to collect three cranial volume measurements. We used nonparametric tests to determine whether the three measures differ between the two groups. Correlations were calculated between age and the three volume measures in each group to determine whether the growth trajectory of the measurements differ between children with right unicoronal synostosis and unaffected infants. RESULTS: Our results show that the three volume measurements are not reduced in infants with right unicoronal synostosis relative to unaffected children. Correlation analyses between age and various volume measures show similar correlations in infants with right unicoronal synostosis compared with unaffected children. CONCLUSIONS: Our results show that the relationship between brain size and intracranial size in infants with right unicoronal synostosis is similar to that in unaffected children, suggesting that reduced intracranial volume is not responsible for alterations of the brain in craniosynostosis.